Longitudinal urinary creatinine excretion values among preadolescents and adolescents. - Martin, Michael D. (2018)
To present longitudinal urinary creatinine excretion data for developmentally normal children 9–17 years of age. Only extremely limited data have been presented of a longitudinal nature for this age group. Overall, 507 children who participated in a prospective, randomized, controlled trial of dental materials safety were followed longitudinally for 7 years with renal measures, including creatinine excretion. Urinary creatinine means, confidence intervals, and 10th, 50th, and 90th percentiles are presented by year of age for the entire group, by sex, and by race (whites, blacks). Urinary creatinine excretion increases with age for both sexes and for both races (P < 0.0001). No significant sexual difference were observed, although a race difference occurs, with blacks showing higher excretion levels than whites (P _ 0.0003). We present longitudinal urinary creatinine excretion data for ages 9–17 in which creatinine excretion increases with age throughout the time period. No sexual differences are observed, although blacks excrete significantly higher levels of urinary creatinine than do whites.